Acute motor axonal neuropathy developing during Helicobacter pylori infection - Gödekmerdan, Ahmet; Kurt, Çıtak Ayşegül Neşe; Kurt, Abdullah; Kabakuş, Nimet (My University, 2004)
-
Keywords: Helicobacter pylori; Helicobacter Infections; Guillain-Barre Syndrome; Nervous System Diseases